Il gioco di permutazioni con ripetizioni nel 'Doppio Sempione' di Elio Vittorini (Prassi Ecdotiche della Modernità Letteraria, 2023)
The game of permutations with repetitions in ‘Doppio Sempione’ by Elio VittoriniA careful research and exploration of Vittorini Collection (Centro Apice, Archivi della Parola, dell’Immagine e della Comunicazione Editoriale – Milano) has brought to light the remaking, for a new publication, of a passage from the novel Il Sempione strizza l’occhio al Frejus by Elio Vittorini (Bompiani 1947). The contribution analyses Vittorini’s writing process which, after a research on all the versions of the manuscripts, can be defined as a ‘game of permutations with repetitions’.
Keywords: Elio Vittorini; Manuscripts; Authorial Philology; Criticism of versions